2005
DOI: 10.1002/da.20046
|View full text |Cite
|
Sign up to set email alerts
|

Standardized clinical outcome rating scale for depression for use in clinical practice

Abstract: The integration of research into clinical practice to conduct effectiveness studies faces multiple obstacles. One obstacle is the burden of completing research measures of outcome. A simple, reliable, and valid measure that could be rated at every visit, incorporated into a clinician's progress note, and reflect the DSM-IV definition of a major depressive episode (including partial and full remission from the episode) would enhance the ability to conduct effectiveness research. The goal of the present study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Interrater reliability for clinician assessed and independent ratings of the GAF scale are excellent (Hilsenroth et al, 2000). Clinician‐rated GAF scores show convergent validity with other scales such as structured ratings of depression (e.g., Zimmerman, Posternak, Chelminski, & Friedman, 2005), interpersonal/relational functioning (Hilsenroth et al, 2000), and social/occupational functioning (Hilsenroth et al, 2000). As noted earlier, research indicates that clinician reports are particularly reliable and valid with regard to adolescent EDs (Couturier et al, 2007).…”
Section: Methodsmentioning
confidence: 93%
“…Interrater reliability for clinician assessed and independent ratings of the GAF scale are excellent (Hilsenroth et al, 2000). Clinician‐rated GAF scores show convergent validity with other scales such as structured ratings of depression (e.g., Zimmerman, Posternak, Chelminski, & Friedman, 2005), interpersonal/relational functioning (Hilsenroth et al, 2000), and social/occupational functioning (Hilsenroth et al, 2000). As noted earlier, research indicates that clinician reports are particularly reliable and valid with regard to adolescent EDs (Couturier et al, 2007).…”
Section: Methodsmentioning
confidence: 93%
“…Recently, Zimmerman et al (2005, 2007) compared remitted patients with different scores on the Hamilton Rating Scale for Depression (HRS-D) and found that patients with a score of 0–2 reported significantly less psychosocial impairment and better quality of life than those with a score of 3–7. This is probably reflective of the fact that the instruments commonly used to assess the severity of depression and residual symptoms are focused on typical aspects (Kennedy and Paykel, 2004; Papakostas et al , 2004; Dombrovski et al , 2007) and overlook atypical symptoms (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical impression supported by available evidence also indicates that real world outcomes in MDD fall short of what is reported in rigorous clinical trials. The disconnect between efficacy and effectiveness outcomes has been understood to be in part a reflection of the different patient populations studied, as the majority of individuals in clinical practice would not be eligible for pivotal trials due to stringent inclusion criteria . Taken together, there is need for understanding the therapeutic effectiveness of treatments in real world practice to inform treatment decisions.…”
Section: Introductionmentioning
confidence: 99%